A diáspora da Igreja Católica de Portugal para a América Portuguesa do século XVIII: o papel religioso, político e cultural do sacramento da penitência e da prática das indulgências - Couto, Carla Cristiane Teixeira do (2010)
This research has proposed a study on the diaspora of the Catholic Church of Portugal for Portuguese America in the eighteenth century, following some of the expansion of Christianity, noting the role of religious, political and cultural development of the Sacraments of Penance and the practice of indulgences. We consider the precepts laid down in Council of Trent and their influence in the process of Portuguese colonization, and remember that this period is marked by the ideas of the Renaissance and Enlightenment movements. By monitoring the administrative and pastoral concerns of the bishops, both in Portugal and in the colony, we realize that the ecclesiastical patronage system represented an obstacle to the action of themselves at dioceses. The character of animosity in relations between Church authorities and representatives of the Crown in the captaincy, especially in the middle of the eighteenth century show that the submission of religious power in the face of ecclesiastical patronage system was not full. Gradually, following the guidelines of Trent, the Church takes form more defined in Cologne